Identification of NAB1, a repressor of NGFI-A- and Krox20-mediated transcription. - Mark W. Russo; Bradley R. Sevetson; Jeffrey Milbrandt (1995)
NGFI-A (also called Egr1, Zif268, or Krox24) and the closely related proteins Krox20, NGFI-C, and Egr3 are zinc-finger transcription factors encoded by immediate-early genes which are induced by a wide variety of extracellular stimuli. NGFI-A has been implicated in cell proliferation, macrophage differentiation, synaptic activation, and long-term potentiation, whereas Krox20 is critical for proper hindbrain segmentation and peripheral nerve myelination. In previous work, a structure/function analysis of NGFI-A revealed a 34-aa inhibitory domain that was hypothesized to be the target of a cellular factor that represses NGFI-A transcriptional activity. Using the yeast two-hybrid system, we have isolated a cDNA clone which encodes a protein that interacts with this inhibitory domain and inhibits the ability of NGFI-A to activate transcription. This NGFI-A-binding protein, NAB1, is a 570-aa nuclear protein that bears no obvious sequence homology to known proteins. NAB1 also represses Krox20 activity, but it does not influence Egr3 or NGFI-G, thus providing a mechanism for the differential regulation of this family of immediate-early transcription factors.